Wpływ Krzywizny i Podatności Ścianki na Stateczność Hydrodynamiczną Laminarnej Nieściśliwej Warstwy Przyściennej (II) - Mzyk, E. (Engineering Transactions, 1971)
An investigation was made of the influence of a longitudinal curvature, rigid and susceptible, on the stability of a laminar by-wall layer in relation to small disturbances of a diagonal vortex type. Among other things, it was assumed that the velocity profile of a basic flow is independent of the curvature and susceptibility of a wall, and the mechanical properties of that wall were described by the four non-dimentional parameters. Results have been obtained in the form of curve neutral stability for various values of nondimentional curvature of a wall for series of combinations of parameters characterizing the mechanical properties of the wall. For the rigid wall, the calculations were made by taking the Blasius velocity profile and a family of profiles of velocities of Pohlhausen with the sixth grade multinomial, and for the deformed wall - only the Blasius profile. In the case of a rigid convex wall, it was assumed that increase in its curvature influences the flow in an unstable manner (from the point of view of an instability of «A-class») only if the mechanical properties of the wall are suitably far from the properties of the rigid wall.